A Brief Study about Supply Chain Finance - Hajar Alawi; Mohammed Abdul Imran Khan (New Innovations in Economics, Business and Management Vol. 8, 2022)
In this chapter, one aspect will be covered: Supply Chain Finance, which is how money flows back, to the suppliers. Generally, supply chain finance is when firms (buyers) pay their invoices to the suppliers (sellers) through a financer/funder (bank or any financial institution). The chapter is a much-needed summary of Supply Chain Finance and its increasing importance. Focusing on Supply Chain Finance, the chapter also draws attention to the development of Supply Chain Finance; its history, advantages, and disadvantages. The objective of this study is to provide learners with a basic understanding of Supply Chain Finance, its concept, benefits, advantages, disadvantages, and how it works. The chapter concludes by analyzing the future prospects of Supply Chain Finance.